Life cycle assessment of an electroless nickel plating wastewater treatment plant - Kamaruddin, Siti Nurhayati (2014)
Electroless nickel plating industry has been a well-known industry compared to other types of electroplating industry. This method of coating practice yields better coating properties. Life Cycle Assessment (LCA) is being proposed to assess and quantify the environmental impacts of the treatment processes which include physical, chemical and biological treatments to identify the hotspot (weak point) in the treatment processes. The methodology of this study followed the basis of International Organization for Standardization (ISO) 14040 - series framework. Life Cycle Inventory (LCI) table was completed by data collection from a plant and added with chemical analysis. The assessment was conducted using GaBi software and Life Cycle Impact Assessment (LCIA) method is referred to ReCiPe method (RIVM, Radboud University, CML and Pré Consultants). Both problem-oriented and damage-oriented methods were assessed and chemical treatment process showed higher impacts in important categories like climate change, acidification and human toxicity. This caused the process to be the hotspot in this wastewater treatment plant. The results for problem-oriented are 1553 kg CO2 equivalent, 5.8 kg SO2 equivalent, and 5.4 kg 1,4 dichlorobenzene (1,4-DB) equivalent respectively and results for damage-oriented are 2.17 x 10-3 DALY (Disability Adjusted Life Years), 3.36 x 10-8 species.yr and 3.80 x 10-6 DALY respectively when compared to the other treatment processes. This was due to the usage of chemicals in the chemical treatment which is significantly higher than in other processes. Hence, two different scenarios were suggested and assessed in order to reduce the environmental impacts of this conventional wastewater treatment. The scenarios include using the chitosan in chemical treatment process and replacing the chemical treatment process with wet air oxidation process. Both processes showed less environmental impacts than the conventional chemical treatment process in the wastewater treatment plant